Small-scale to large-scale and back: larval trematodes in Lymnaea stagnalis and Planorbarius corneus in Central Europe - Brown, Rebecca; Soldánová, Miroslava; Barrett, John; Kostadinova, Aneta (Parasitology research, 2011)
We examined the small-scale temporal and spatial variability in composition and structure of larval trematode communities in Lymnaea stagnalis and Planorbarius corneus in two fish ponds in the Czech Republic and compared the patterns of richness and similarity to continental and regional trematode faunas of these hosts. The levels of parasitism in the populations of both hosts were high, the former parasitized predominantly by allogenic species maturing in a wide range of birds and the latter infected by relatively more species completing their life cycles in micromammals. Communities in both hosts exhibited a congruent pattern of seasonal change in overall infection rates and community composition with lower levels of infection in spring. Both temporal and spatial variation was closely related to the structure of snail populations, and no significant differentiation of community composition with respect to pond was observed. Comparisons with large-scale inventories revealed overall congruent patterns of decreased richness and similarity and increased variability at the smaller scales in both host-parasite systems. The relative compositional homogeneity of larval communities in both snail hosts irrespective of scale suggests that historical data at small to medium regional scales may provide useful estimates of past richness and composition of larval trematode communities in these snail hosts.
Keywords: Česká republika; plži; Czech Republic; Gastropoda; Animals; roční období; Seasons; zvířata; Lymnaea; Trematoda